Naf - Yeled Rehov - Alafi, Moshe (Israel : Alafim Productions, 2006)
A documentary about a homeless boy's life filmed over a two and a half year period. Naf (Naftali) is an ultra-orthodox Jewish boy thrown out of his parents' home for being a "bad apple." From the age of 14 he wanders the streets of Jerusalem, being exposed to crime, violence, and sexual abuse. Only fighting keeps him alive. He fights the city council as a representative of homeless youth; through the court system, he fights the man who sexually abused him; and he lobbies radio stations to play his music. A story about struggle for survival.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films